PENGUKURAN STATUS GIZI DAN PENGENALAN MAKANAN SEHAT PADA ANAK USIA DINI DI TK KALAM KUDUS MEDAN - Juniwati Barus, Darwita; Henny Arwina Bangun; Taruli R Sinaga; Cinthia Agnes (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2025)
Background: Early childhood education, such as kindergarten (TK), plays a crucial role in establishing the foundation for children's physical and cognitive development. Early childhood growth significantly impacts children's health, which is greatly influenced by the quantity and variety of food they eat. Nutritional problems in toddlers and young children remain a serious issue in Indonesia, with high prevalences of stunting, wasting, underweight, and overweight. All of these conditions are caused by an imbalance between nutritional intake and a child's body needs, which can negatively impact their health and cognitive development in the future. Furthermore, this can also increase a child's risk of disease and death. Objective: This study aims to examine the nutritional status of toddlers using indicators of height/age, weight/age, and height/weight. Method: This research is descriptive with sampling technique using total sampling which is done by taking all respondents who were at the time of the research as many as 37 children of Kalam Kudus Kindergarten Medan consisting of PAUD and Kindergarten A and Kindergarten B. Results: It was found that there were 37.85% indicators of TB/U nutritional status in the short and very short group 2.70% and there were 5.40% who were tall, Indicators of BB/U nutritional status in the less category 13.52% and very less nutrition 5.4% and 24.32% in the overweight category. Indicators of TB/BB nutritional status in the very less category 5.4%, less 13.52% and more risk 10.82% and more (obesity as much as 13.51%. Conclusion: It is hoped that there will be attention from parents regarding the provision of food at home, breakfast and provisions to be brought to school, teachers can also provide motivation and interesting games about healthy and nutritious food.